Global research trajectories in gut microbiota and functional constipation: a bibliometric and visualization study - Ong, Shun Seng; Xu, Lianjie; Ang, Ching Wei; Deng, Xiaoyue; Lu, Hai; Xu, Tianshu (Frontiers in Microbiology, 2024)
BackgroundFunctional constipation (FC) negatively impacts quality of life and is associated with gut microbiota (GM) imbalances. Despite the growing interest in this area, a thorough analysis of research trends is missing. This study uses bibliometric methods to assess the global research on GM’s role in FC, pinpointing key topics, impactful studies, and prominent researchers to guide future research and identify gaps.MethodsIn our study, we conducted a performance analysis and science mapping using bibliometric indicators such as publication trends, author and institutional contributions, productivity, impact, keyword analysis, and collaboration networks. We employed software tools like VOSviewer, Biblioshiny, CiteSpace, and SCImago Graphica to automate the assessment of metrics including country, institutional, and journal distribution, authorship, keyword frequency, and citation patterns.ResultsFrom 2013 to 2024, annual publications on GM and FC rose from 29 to 252, with a slight decrease to 192 in 2024. Average citations per publication peaked at 11.12 in 2021, declining to 6.43 by 2024. China led in research output (37.8%), followed by the United States (14.4%) and Japan (7.5%). Bibliometric analysis identified key authors like CHEN W and ZHANG H, with 30 and 27 articles, respectively. Jiangnan University and Harvard University were top contributors, with 131 and 81 articles. Keywords analysis revealed “constipation,” “gut microbiota,” and “probiotic” as central themes, with a shift toward “gut microbiota” and “intestinal flora” in recent years. This study provides a comprehensive overview of the research landscape, highlighting leading authors, institutions, and evolving research priorities in the field.ConclusionOur review synthesizes current GM and FC research, guiding future studies. It suggests exploring GM in various GI disorders, the impact of lifestyle and drugs on GM, advanced research techniques, and probiotics/prebiotics for FC. There’s also a focus on therapies targeting GM’s effect on the gut-brain axis, paving the way for improved FC management.